Introduction to Islamic Sukuk and Its benefits in Current Economy: اسلامی صکوک کاتعارف اورموجودہ معیشت میں اس کےفوائد - Hannan, Dr. Abdul; Sadiq, Dr. Muhammad; Ahmed, Zahoor (Al Khadim Research Journal of Islamic Culture and Civilization, 2023)
<span style="font-size: 10.0pt; font-family: 'Cambria',serif; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: 'Courier New'; color: #202124; mso-font-kerning: 0pt; mso-ligatures: none; mso-ansi-language: EN;"> There are basically three economic systems running in the world capitalism; and planned economies, which include communism and socialism and Islamic economic system. There is no doubt that the Islamic economic system is the only system that is the most useful and effective for humanity. The basis of the system is divine revelation, which is safe from all kinds of mistakes. And Muslim scholars, keeping in front of the new challenges in the current economy, have come up with a viable solution for the Muslim Ummah in the light of the Qur'an and Hadith, which can compete with the capitalist and cooperative system. An important part of this chain is Islamic Sukuk and the use of Sukuk in the Islamic economy is increasing day by day. In this article, the introduction of Islamic Sukuk and its reality along with its use and benefits in the current economy have been discussed. https://doi.org/10.5281/zenodo.10519425